Determinants of personal bankruptcy discharge in Malaysia: A social capital approach of Al-Nahd and Ta’awun - Isa, Ahmad Mahir; Ahmad, Nor Hayati; Zainol, Zairy (UUM Press, 2021)
This study investigates the relationship between Gross Domestic Product (GDP), Consumer Price Index (CPI), Unemployment Rate (UE), Interest rate (IR), Household Debt (HD) on bankruptcy discharge and test the application of an Islamic concept of mutual cooperation, Social Relief Fund (SRF) to enhance the bankruptcy discharge. The study period is from 2000 to 2019. The autoregressive distributed lag (ARDL) was used in the study. Two models were tested; Model 1 consists of the macroeconomic variables without SRF and Model 2, with SRF. Model 1 shows none of the variables has significant effect on bankruptcy discharge for long run relationship. However, Model 2 shows GDP, CPI and SRF have significant positive long run relationship with bankruptcy discharge. This provides statistical evidence that SRF has a beneficial long-run relationship to enhance bankruptcy discharge in Malaysia. For short run relationship, Model 1 reveals GDP, CPI, and UE as significant variables to discharge. Model 2 shows stronger short run relationships in which GDP, IR, HD, SRF are positive, and CPI is negative to bankruptcy discharge. These variables are significant at 1 percent level. The findings contribute new knowledge on determinants of bankruptcy discharge in Malaysia. The study provides empirical evidence that SRF is a potential component as a social safety net in providing financial assistance among distressed debtors from bankruptcy. We recommend the use of SRF as the current bankruptcy reform is being viewed from the legislative lens and lacks the social capital component to assist debtors achieve financial restitution.